2022
DOI: 10.1159/000523869
|View full text |Cite
|
Sign up to set email alerts
|

Serodominance Profile in a Dust Mite Complex Region

Abstract: <b><i>Background/Objective:</i></b> The objective of this study was to describe the molecular sensitization profile of mite allergy in an area with a high environmental exposure of house dust mites (HDM) and storage mites. <b><i>Methods:</i></b> Skin prick tests were performed with standardized extracts (DIATER, Madrid, Spain). A specific commercial molecular panel (MADx) for <i>Dermatophagoides pteronyssinus</i> (Dpt), <i>Dermatophagoides farin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 20 publications
5
10
2
Order By: Relevance
“…The analysis with the use of Bayesian network has confirmed the fact that the most probable sensitivity in individual patient profiles is the simultaneous sensitivity to allergens of groups 1 and 2, as well as to Der p 23. The major significance of sensitization to group 1 and 2 allergens as well as to Der p 23 in the study population is consistent with the data of other authors [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The analysis with the use of Bayesian network has confirmed the fact that the most probable sensitivity in individual patient profiles is the simultaneous sensitivity to allergens of groups 1 and 2, as well as to Der p 23. The major significance of sensitization to group 1 and 2 allergens as well as to Der p 23 in the study population is consistent with the data of other authors [29].…”
Section: Discussionsupporting
confidence: 92%
“…[35,36] According to the data presented in scientific papers, Der p 7 is associated with the development of allergic rhinitis and sensitization to Der f 2, Der p 2 and Der p 23 increases the risk of developing atopic dermatitis. At the same time, sensitization to Der p 10 reduces the risk of atopic dermatitis development [29]. Our data indicate that such effect may be connected with the absence of sensitization to group 1 and 2 allergens as well as to Der p 23 in patients whose profiles contain Der p 10 as CPD of sensitization to Der f 1, Der f 2, Der p 20 and Der p 23 increased up to 68.43% if Der p 10 was absent in the profile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…to the middle and minor group of allergens, were lower than the literature. 8,22,28,36 We believe this difference may be attributed to the younger age of our study group. Conversely, the positivity ratios for Der p 10 (19.7%) also known as tropomyosin and Der p 20 (19.7%) were higher than reported in the literature.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 82%
“…Conversely, the positivity ratios for Der p 10 (19.7%) also known as tropomyosin and Der p 20 (19.7%) were higher than reported in the literature. 22,28 Tropomyosin, 37 an allergen found in various sources such as mites, cockroaches, shellfish, anisakis, mealworms, and fruit flies [38][39][40] has prompted inquiries into the primary sensitization source. Our study revealed that over two-thirds of tropomyosin sensitizations were selective, reducing the likelihood of mites as the primary source.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Even though sIgE-array platforms have included a wide spectrum of HDM allergens (8,14), only Der p 1, Der p 2, Der p 23, and Der p 10 (tropomyosin) are currently available for the component-resolved diagnosis of HDM allergy on ImmunoCAP. Our results, using InmunoCAP in the largest sample published to date, are similar to those previously reported in terms of prevalence of sensitization (6,8,14,15,17) but we report a high rate of monosensitization to Der p 23 (6,8,(15)(16)(17)(18)20,21). The clinical relevance of Der p 23 is only partially defined, and the prevalence and relevance of the exclusive sensitization to it has received little attention so far.…”
Section: Discussionmentioning
confidence: 99%